POTENSI PENDAPATAN ASLI DAERAH DALAM RANGKA PELAKSANAAN OTONOMI DAERAH - Khairul Umam, Irfan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Local Revenue Potential in the Context of Regional Autonomy in Indramayu. Abstract: Demands to increase revenue (PAD) greater, together with the increasing number of delegation of authority from the central government to local governments. Financial transfers made by the central government to local governments through equalization funds are relatively adequate for the implementation of regional autonomy, nevertheless required local governments to explore more creative fullest potential local funding sources, as this greatly helps to increase accountability and flexibility in the use of Budgets. The results showed that the acceptance of the PAD consists of local taxes, levies, wealth management outcomes separated areas as well as other PAD legitimate and execution of the collection is done by the work unit or related agencies. Keywords: PAD, Autonomy, Indramayu district Abstrak: Potensi Pendapatan Asli Daerah Dalam Rangka Pelaksanaan Otonomi Daerah di Kabupaten Indramayu. Tuntutan untuk meningkatkan pendapatan asli daerah (PAD) semakin besar, berbarengan dengan semakin banyaknya pelimpahan kewenangan dari pemerintah pusat kepada pemerintah daerah. Transfer keuangan yang dilakukan oleh pemerintah pusat kepada pemerintah daerah melalui dana perimbangan jumlahnya relatif memadai dalam rangka pelaksanaan otonomi daerah, walaupun begitu pemerintah daerah diharuskan lebih kreatif untuk menggali secara maksimal sumber pembiayaan daerah yang potensial, karena hal ini sangat membantu meningkatkan akuntabilitas dan keleluasaan dalam penggunaan APBD. Hasil penelitian menunjukkan bahwa penerimaan PAD terdiri dari pajak daerah, retribusi daerah, hasil pengelolaan kekayaan daerah yang dipisahkan serta lain-lain PAD yang sah dan pelaksanaan pemungutannya dilakukan oleh unit kerja atau dinas-dinas terkait. Kata Kunci: PAD, Otonomi Daerah, Kabupaten IndramayuDOI:10.15408/sjsbs.v1i2.1549